Overuse of symptomatic medications among chronic (transformed) migraine patients: profile of drug consumption - Abouch Valenty Krymchantowski (Arquivos de Neuro-Psiquiatria)
Chronic daily headache and chronic (transformed) migraine (TM) patients represent more than one third of the subjects seen in specialized headache centers. Most of these patients may overuse symptomatic medications (SM) taken on a daily basis to relieve headache and associated symptoms. The conversion to the daily or near-daily pattern of headache presentation is thought to be related to the medication overuse. The aim of this study was to evaluate the profile of SM consumption among transformed migraine patients attending a tertiary center. One hundred thirty three consecutive patients (22 men and 111 women, ages 17 to 80) with TM and overuse of SM according to the proposed criteria of Silberstein et al (1994, 1996) were prospectively studied. None of the patients were under treatment for other conditions. Among them, 73 (54.9%) were using one category of SM, while 55 (41.3%) and 5 (3.8%) patients were taking simultaneously two and three categories of SM respectively. The categories of overused symptomatic medications varied from simple analgesics to narcotics, triptans and combinations of ergot derivatives and caffeine and of analgesics and caffeine. The average intake per patient per day was of 3 to 4 tablets and mostly of the patients overused simple analgesics (isolated or in combination with other substances) (75.2%), caffeine containing drugs (71.4%), drugs containing ergotamine derivatives (26.1%), triptans (alone or combined) (15.5%), drugs with narcotics or ansiolitics (13%) and anti-inflammatory drugs (3.7%). The mechanisms by which the overuse of symptomatic medications may play a role in this transformation are uncertain but despite of the necessity of controlled trials to demonstrate the real role of such compounds in the development of transformed migraine, this study emphasizes the necessity for more rigorous prescribing guidelines for patients with frequent headaches.